Joseph Conrad : a literary life (Mac millan, 1989)
A sketch of Conrad's varied cultural background (emphasising the Polish aspect) provides a biographical outline for this study, which then concentrates on the progress of Conrad's literary career, paying particular attention to his economic circumstances and the milieu of publishing.